2016
DOI: 10.1007/s40279-016-0507-z
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training as a Tool for Preventing and Treating Musculoskeletal Disorders

Abstract: The aging process is characterized by several physiological, morphological, and psychological alterations that result in a decreased functional and health status throughout the life span. Among these alterations, the loss of muscle mass and strength (sarcopenia) is receiving increased attention because of its association with innumerous age-related disorders, including (but not limited to) osteoporosis, osteoarthritis, low back pain, risk of fall, and disability. Regular participation in resistance training pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 114 publications
0
56
0
3
Order By: Relevance
“…Thus, it can be stated that eccentric training of the knee extensors is very cost-effective. It has been shown by previous studies that conventional resistance training is beneficial for elderly population to minimize and prevent sarcopenia that could lead to chronic diseases (Booth et al, 2012; Pedersen and Saltin, 2015; Ciolac and Rodrigues-da-Silva, 2016). It is well documented that exercise is medicine and many chronic diseases can be prevented and treated by exercises (Pedersen and Saltin, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can be stated that eccentric training of the knee extensors is very cost-effective. It has been shown by previous studies that conventional resistance training is beneficial for elderly population to minimize and prevent sarcopenia that could lead to chronic diseases (Booth et al, 2012; Pedersen and Saltin, 2015; Ciolac and Rodrigues-da-Silva, 2016). It is well documented that exercise is medicine and many chronic diseases can be prevented and treated by exercises (Pedersen and Saltin, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One negative aspect of performing eccentric contractions is potential muscle damage characterized by delayed onset muscle soreness (DOMS) and a prolonged loss of muscle function (Clarkson et al, 1992; Howatson and van Someren, 2008; Gómez-Cabello et al, 2012; Hody et al, 2013; Jamurtas et al, 2013). Greater muscle damage is induced when eccentric contractions are performed without prior experience or with a long interval from a previous exposure to similar eccentric contractions (Howatson and van Someren, 2008; Hody et al, 2013; Hyldahl and Hubal, 2014; Ciolac and Rodrigues-da-Silva, 2016). However, it has been shown that preconditioning exercise consisting of low-intensity eccentric contractions that do not induce any symptoms of muscle damage, is effective for attenuating severe muscle damage potentially induced by maximal eccentric exercise (Chen et al, 2012, 2013).…”
Section: Introducionmentioning
confidence: 99%
“…We hypothesized that, because of the limited joint pain-related muscular performance commonly found in knee OA patients 7, 16, the use of two isokinetic assessments with a short period of recovery between tests (2 min) would not have a motor learning effect in the present study. However, the increased knee extension and flexion TQ PEAK , TQ PEAK /BW, and total work, as well as the lower knee extension and flexion CV observed in Test 2, suggest there was a motor learning effect during the second isokinetic assessment, as observed in healthy postmenopausal women 9.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle strength plays an important protective role in the progression of knee OA 5-7, and it is inversely associated with physical function in this population 2, 3, 8. Therefore, evaluation of the muscular performance may have important implications to counteract the effects of its reduction on knee OA pathophysiology 2, 3, 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation